SME BUSINESS PERFORMANCE OF A BIBLIOMETRIC ANALYSIS - Nor Razuana Amram; Muhammad Asyraaf Hashim (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Bibliometrics involves the systematic combination, analysis, and evaluation of bibliographic information derived from scientific publications. This study aims to the literature on Small and Medium Enterprises (SME) business performance by proposing ten research clusters where scholars can expand business performance research to facilitate effective performance for SME. The study reviewed articles on SME business performance published in the Scopus database between 1996 and February 2025, employing well-established bibliometric techniques and analyzing the data using VOSviewer software. A total of 429 articles published in the past decade were evaluated, focusing on trends in publication patterns, prominent authors, affiliated organizations, countries, frequently cited articles, and recurring themes. This analysis provided insights into the key research topics that have captured researchers’ attention in recent years. Surprisingly, the findings revealed limited collaboration among authors, universities, and countries working on SME business performance. In conclusion, bibliometric analysis offers valuable insights into research on SME business performance. By applying this approach, the study contributes to the understanding and promotion of this critical topic, benefiting scientific journals, academics, and institutions in advancing knowledge within the field of education.